The Morals of Life that Thirumanthiram Depicts - G, Kokila (International Research Journal of Tamil, 2022)
He created 3000 Tamil mantras through tricks. Tact means maturity. Discipline is essential to reach that level. Thirumoolar describes the method of running the flow. Thirumanthiram is a biographical philosophy. A book that can be realized through the experiential knowledge that comes through practice with effort. This book is variously praised as a devotional book, a scriptural book, a hymn book, a skill book, a godly book, a yoga book, and a knowledge book. However, the book that guides life is its uniqueness. The guidebook is unique. The research results say that due to his unparalleled yoga training and the power of meditation, Thirumoolar excelled in the techniques of protecting the body for many years and blessed those who had lived in this world for a long time and attained full enlightenment. Consider that all newborn children should attain enlightenment. The study will focus on love, living without suffering, living with the body, medicine, and virtue related to human life. Therefore, in this article, we will see the life thoughts given by Thirumoolar.